Beluga whale (Delphinapterus leucas) behaviour in the presence of whale-watching vessels - Westdal, Kristin H.; Richard, Pierre R.; Sportelli, Jessica; Gillis, Erica; Ferguson, Steve H. (Frontiers in Marine Science, 2023)
Beluga whales (Delphinapterus leucas) are social animals that return to the same estuaries each summer season. The Western Hudson Bay belugas in the Churchill River estuary appear to be attracted to boats, resulting in whale-watching being a popular tourism activity for the area. However, regulators have raised concerns about whether this activity has negative consequences on the beluga population. We hypothesized that more vulnerable groups, such as groups containing calves, would avoid whale-watching vessels, while juvenile groups, who appear to have a more developed curiosity, would be more likely to interact with vessels. To test these hypotheses, behavioural observations were conducted in 2019, 2020, and 2021, in the estuary using a similar methodology to a study conducted in 2005 and 2006. An increase in tourism since that initial study offered a unique opportunity to compare potential change over time. In this study, a group of whales was randomly selected; group type, initial behaviour type, distance to vessel, and observed behaviour with distance to vessel during three-minute focal follows were recorded. The same method was also applied from shore and we compared frequencies of whale behaviour during experimental (vessels present) and control (vessels greater than 300m away) periods. Results showed that there was a significant difference in the mean group size of belugas in the presence of vessels compared to those observed in the absence of vessels. There was also a significant difference in beluga behaviour as well as a significant behavioural difference between age class of belugas in the presence of vessels, compared to their behaviour in absence of vessels. During focal follows from vessels, belugas spent 63% of their time interacting with vessels, when within 25 m of a vessel, an increase from the 48% observed from the previous study conducted 15 years previous. Our results overall showed beluga behaviour differed in the experimental compared to control settings but suggest that those belugas’ reactions to vessels are not necessarily deleterious to them, in that direct interactions with wildlife are low and unlikely to carry risk, and that they may have habituated to whale-watching vessels over the last two decades.